Typification of the North American species of Trillium subg. Trillium (Melanthiaceae: Parideae) - Floden, Aaron J.; Wesley M. Knapp (Phytotaxa, 2023)
Here we provide type information and synonymy for the accepted North American species of Trillium subg. Trillium and notes on the distribution and character variation for some species. Lectotypes are designated for T. flexipes, T. rugelii and T. vaseyi. We also lectotypify the names T. cernuum var. declinatum f. billingtonii and T. cernuum var. declinatum f. walpolei, which have been associated with both T. cernuum and T. flexipes; T. cernuum f. tangerae; and T. rhomboideum var. album (=T. rugelii), which has often been associated with T. erectum.